Approaching minimum area polygonization - Taranilla, María Teresa (2011)
The problem of fi nding a minimum area polygonization for a given set of points in the plane, Minimum Area Polygonization (MAP) is NP-hard. Due to the complexity of the problem we aim at the development of algorithms to obtain approximate solutions. In this work, we suggest di feerent strategies in order to minimize the polygonization area.We propose algorithms to search for approximate solutions for MAP problem. We present an experimental study for a set of instances for MAP problem.